2017
DOI: 10.2147/jmdh.s144526
|View full text |Cite
|
Sign up to set email alerts
|

Establishing community-based integrated care for elderly patients through interprofessional teamwork: a qualitative analysis

Abstract: BackgroundWorking in multidisciplinary teams is indispensable for ensuring high-quality care for elderly people in Japan’s rapidly aging society. However, health professionals often experience difficulty collaborating in practice because of their different educational backgrounds, ideas, and the roles of each profession. In this qualitative descriptive study, we reveal how to build interdisciplinary collaboration in multidisciplinary teams.MethodsSemi-structured interviews were conducted with a total of 26 med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 17 publications
1
44
0
2
Order By: Relevance
“…[17][18][19] Community-based education (CBE) is suggested as a model for facilitating IPE in collaborative skills in the workplace. [20][21][22] CBE is defined as learning activities that use the community extensively as a learning environment, in which not only students but also teachers, members of the community, and representatives of other sectors are actively engaged throughout the educational experience. 23 Community-based IPE (CBIPE) is the process by which a group of two or more students from different health-related occupations with different educational backgrounds learn together while utilising the community as a learning environment, with collaboration and interaction as part of their learning goals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19] Community-based education (CBE) is suggested as a model for facilitating IPE in collaborative skills in the workplace. [20][21][22] CBE is defined as learning activities that use the community extensively as a learning environment, in which not only students but also teachers, members of the community, and representatives of other sectors are actively engaged throughout the educational experience. 23 Community-based IPE (CBIPE) is the process by which a group of two or more students from different health-related occupations with different educational backgrounds learn together while utilising the community as a learning environment, with collaboration and interaction as part of their learning goals.…”
Section: Introductionmentioning
confidence: 99%
“…27 Various approaches to CBIPE have been previously reported such as learning in rural and primary healthcare settings, 24,28,29 community-based learning within broader community context 16,22,30 and for specific community context; the commonly used model of CBIPE in the western countries. 21,[31][32][33][34][35] The nature of interprofessional learning activities is mainly to provide healthcare services primary healthcare setting, not in the community. Examples of CBIPE in specific community contexts have often been limited to specific settings like senior housing 32 or child healthcare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the framework of the community-based integrated care system, interprofessional education has been the focus of increasing attention 9 , 10 , 11 ) . Interprofessional discussions concerning patient care planning are commonly facilitated within the Japanese long-term care insurance system 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that communication and collaboration skills increased, and also they were satisfied with their collaborative practice by participating in the community-based interprofessional education programs. [9][10][11][12] The Faculty of Medicine, Universitas Diponegoro, as one of the health education institutions in Central Java, has taken the responsibility to help the local government to increase maternal health by implementing the IPE program in the community. This program has recently been implemented in collaboration with the health district and primary health center.…”
Section: Introductionmentioning
confidence: 99%